Pathogenicity of Some Entomophatogen’s Fungus (Lecanicillium lecanii, Metarhizium anisopliae, and Beauveria bassiana) to Aphis glycines on Soybean - riri widariyanto; Mukhtar Iskandar Pinem; Fatimah Zahara (Universitas Sumatera Utara, 2017)
Soybean aphids (A. glycines) are the important pests and major vector virus SMV(Soybean Mosaic Virus) on soybeans. Control techniques which performed by the used of insectisides is not effective and leaves residue on the environment. Entomophatogen’s fungus is a safe alternative control for the environment. This research isaimed to determine the effectiveness of entomopatogen’s fungus (L. lecanii, M. anisopliae, and B. bassiana) to A. glycines on soybean in the field and carried out at experimental field of Faculty of Agriculture of University of Sumatera Utara, from December 2015 until Februari 2016. It used non factorial randomized block design by treatment : Control (Fourth instar of A. glycines without treatment entomopathogen), P1 (Second instar of A. glycines + L. lecanii), P2 (Second instar of A. glycines + B. bassiana), P3 (Second instar of A. glycines + M. anisopliae), P4 (Fourth instar ofA. glycines + L. lecanii), P5 (Fourth instar of A. glycines +B. bassiana), P6 (Fourt instar of A. glycines + M. anisopliae).The results showed thatL. lecanii and M. anisopliaesignificantly effective to reduce A. glycines population with high mortality and fast death time. The highest mortality (90%) is P4 treatment whereas the lowest mortality (37,5%) at P5 treatment. The fastest death time (5 day) is P6 treatment whereasthe longest death time(6,4 day) at P5treatment.